Evaluation of damping effect of perforated plate on the first resonant wave height of liquid sloshing under pitching excitation utilized by CFD - Yuto ARAKI; Akane UEMICHI; Yudai YAMASAKI; Shigehiko KANEKO (Nihon Kikai Gakkai ronbunshu, 2018)
As a method for mining offshore gas fields, a floating production, storage and offloading (FPSO) system is attracting attention. However, sloshing in the oil-gas separator installed in FPSOs excited by sea waves is expected to cause significant difficulties. To suppress sloshing wave heights, one possibility may be to install perforated plates in a tank. In this study, a method is proposed for the accurate estimation of the first resonant wave height in the horizontal cylindrical tank with a perforated plate under pitching excitation in less time. To accomplish this purpose, the pressure loss due to the perforated plate in the open channel must be estimated accurately. Therefore, the pressure loss is modeled using steady CFD calculations considering the effects of the distribution of the flow velocity and the distribution of the inflow angle. The first order sloshing wave height is calculated in the theoretical analysis by substituting the pressure loss calculated in steady CFD. The wave heights determined using the pressure loss utilized by steady CFD are compared with the experimental value measured with a small-scale model. Using the method proposed in this study, the first resonant wave height of sloshing wave height is calculated accurately in less time.